The Mechanism of Elizabethkingia miricola Infection of the Black Spotted Frog as Revealed by Multi-Omics Analysis - Qingcong Wei; Dan Wang; Kaijin Wei; Bin Xu; Jin Xu (Fishes, 2024)
Elizabethkingia miricola (E. miricola) is a significant pathogen that causes the crooked head disease in black spotted frogs. This disease has plagued numerous frog farms in China and has resulted in substantial losses to the frog farming industry. Nonetheless, the exact mechanism that causes the disease in frogs remains unknown. In this study, transcriptomic and microbiomic analyses were conducted to analyze frog samples infected with E. miricola to reveal the infection mechanism of the pathogen. Liver transcriptomic analysis indicated that the livers of infected frogs had 1469 differentially expressed genes when compared with an uninfected group. These DEGs are mainly involved in immunity and metabolism, including neutrophil extracellular trap formation, the NOD-like receptor signaling pathway, leukocyte transendothelial migration, chemokine signaling pathway, Fc gamma R-mediated phagocytosis, and “metabolism”-related pathways such as the pentose phosphate pathway, carbon metabolism, glycerophospholipid metabolism, and glycerolipid metabolism. Similarly, 4737 DEGs were found in the kidney of infected frogs. These DEGs are mainly involved in immunity, including neutrophil extracellular trap formation, the NOD-like receptor signaling pathway, B cell receptor signaling pathway, C-type lectin receptor signaling pathway, complement and coagulation cascade, and Toll-like receptor signaling pathway. Ten immune-associated DEGs were screened in liver and kidney DEGs, respectively. And it was hypothesized that E. miricola infection could influence the host immune response. Microbiome analysis results showed that some opportunistic pathogens such as Citrobacter, Shigella, and Providencia were significantly elevated (p < 0.05) in infected frogs. Additionally, functional prediction confirmed that most of the microbiota in infected frogs were linked to metabolism-related KEGG pathways. In this study, the screened genes linked to immunity showed an association with the gut microbiome. The majority of these genes were found to be linked with the abundance of opportunistic pathogens. The results showed that E. miricola infection led to the downregulation of immune and metabolic-related genes, which led to the inhibition of immune function and metabolic disorder, and then increased the abundance of opportunistic pathogens in the gut microbiota. The findings of this study offer a preliminary foundation for comprehending the pathogenic processes of E. miricola infection in black spotted frogs.